Factors Driving Consumer Impulse Buying On Fashion Products at Tiktok Live - Kaniati, Sandra Putri; Sosianika, Adila; Setiawati, Lina (Politeknik Negeri Bandung, 2024)
The TikTok live-streaming commerce trend is swiftly gaining popularity in Indonesia, with numerous local fashion brands effectively capitalizing on this opportunity to boost their sales within a short timeframe. Previous research suggests that impulsive buying behavior serves as the underlying factor for this phenomenon. Hence, this research was carried out to investigate consumer behavior in live-streaming commerce, aiming to assist small-scale fashion businesses in enhancing their sales. The Stimulus Organism Response (SOR) Model uses price promotion, promotion time limit, streamer-consumer interaction, and consumer-consumer interaction to influence the consumer’ impulsive buying by perceived risk. The quantitative approach collected 445 data from Indonesia TikTok active users who have watched a fashion broadcast and have purchased during the broadcast. The result found that perceived risk significantly affects consumer impulsive buying behavior. The price promotion, promotion time limit, and consumer-consumer interaction were found to have a strong influence on perceived risk. Then, perceived risk-mediated promotion time limit and impulsive buying decision. It means that promotional time limits indirectly affect impulsive buying decisions. Thus, developing effective price promotion, promotion time limit, and consumer-consumer interaction strategy to drive their perceived risk making a purchase, and arrange an impactful promotion time limit tactic.